البنيات الإيقاعية في فواصل السور المكية: أثرها الصوتي ودورها الفني - نصير، أحمد عبدالله أحمد (جامعة بني سويف - كلية الآداب, 2024)
هذه دراسة تطبيقية للجرس القرآني بإيقاعه النغمي ودوره الجمالي، حيث تتناول النسق الإيقاعي الذي اشتملت عليه أصوات فواصل سور (القمر والواقعة والحاقة والغاشية والقارعة)، تلك السور المكية التي تفردت بين جميع سور القرآن بمزايا عديدة، نجملها في النقاط التالية: 1- اشتملت السور المكية على بنيات إيقاعية، تذيلت بها فواصل آياتها، فنشأ عنها إيقاع قرآني بلغ بسبب أبعاده المختلفة درجة في الإعجاز الصوتي كبرى؛ لأنه لم يؤد دوراً صوتياً جمالياً فقط، بل أدى دوراً روحياً أيضاً، فراح يخاطب العقول ويغزو القلوب ويؤثر في النفوس، فما من أحد يسمع سورة من السور المكية ذات البنيات الإيقاعية إلا تحركت لا تساق أصوات فواصلها مشاعره، وتجاوبت مع حسن أدائها عواطفه، ولم يكن له بد من التوفر على الإصغاء إلى القرآن إن كان سامعاً، أو الاسترسال فيه إن كان قارئاً. 2-الإيقاع القرآني النابع عن الفواصل القرآنية ذات البنيات الإيقاعية في السور المكية كان ضرورة فنية تطلبها النص التشريعي في بداية نزول القرآن في مكة؛ لكي يجعل الآذان إليه مصروفة، والقلوب إليه مشدودة، وبالتالي خدم الدعوة الإسلامية في بداية عهدها، وأسهم في انتشارها عن طريق جذب القلوب والأرواح لسماع الكلام السماوي. 3-البنيات الإيقاعية في فواصل السور المكية فسرت لنا جانباً من أسرار حلاوة القرآن الساحرة التي حس بها فصحاء العرب القدماء وبهرتهم وأذهلتهم دون أن يدركوا كُنْهَهَا... This is an applied study of the Quranic rhythm with its intonation and artistic effect (aesthetic and affective), which tackles the rhythmic pattern of the sounds of breaks of the Quranic Surahs of Al-Qamar (the Moon), Al-Qaria (The Calamity), Al-Haqqah (The Inevitable Hour), Al- Ghashiya (the overwhelming Event), and Al-Qariaah (The Day of Noise and Clamour). All those Meccan Surahs have the following distinctive rhythmic characteristics:1- They have rhythmic structures at their verses breaks which produce a type of Quranic rhythm that, thanks to its artistic effect, reach the apex of phonemic miracle. The Quranic rhythm does not only play an aesthetic role, but also a spiritual one, speaking to the minds, hearts and souls, so that no one listens to those Meccan Surahs without their emotions and feelings being greatly moved. The rhythmic pattern is so captivating that it invites reciters and listeners into further experiencing of its beauty. 2- The Quranic rhythm at the breaks of those Meccan Surahs is found to be a technical necessity dictated by the legislative text at the early beginning of the revelation period of the Quran in Makkah, as it is needed to have ears and hearts contemplate and taste it, which did the Islamic propagation further boost allowing human souls to attend to the heavenly words. 3- The rhythmic structures latent at the breaks of the Meccan Surahs explain to us an aspect of the enchanting sweetness of the Quran that astonished the old eloquent rabs even without them articulating the reason.
Keywords: القرآن الكريم -- السور والآيات -- البنيات الإيقاعية -- الفواصل القرآنية